2018
DOI: 10.1002/celc.201800737
|View full text |Cite
|
Sign up to set email alerts
|

The Impedance Response of a Passive Film Revisited by a Double Modulation Technique

Abstract: The interfacial capacitance measured in electrochemical experiments is usually considered to be independent of the faradaic processes involved at the electrode surface. In this work, we report on the use of a double modulation technique, which allows the simultaneous measurement of electrochemical impedance spectroscopy (EIS) and modulation of the interfacial capacitance transfer function (MICTF). We show that the capacitance ascribed to the response of passive films formed on pure iron electrodes in phosphori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
2
0
0
Order By: Relevance
“…3), indicated that the surface coverage by the adsorbed species also increased with the potential. Such a behavior is in agreement with the relaxation of adsorbed species [37,61] and also with the increase of the H 2 formation when the potential of the Mg electrode is shifted towards anodic values. It is thus proposed that the NDE occurs only with theMg þ ads , and expresses as…”
Section: Kinetics Modelsupporting
confidence: 85%
“…3), indicated that the surface coverage by the adsorbed species also increased with the potential. Such a behavior is in agreement with the relaxation of adsorbed species [37,61] and also with the increase of the H 2 formation when the potential of the Mg electrode is shifted towards anodic values. It is thus proposed that the NDE occurs only with theMg þ ads , and expresses as…”
Section: Kinetics Modelsupporting
confidence: 85%
“…(5.4)) the increase of the magnitude of the inductive loop, observed on the EIS diagrams as a function of the applied potential (Figure 5.14), indicated that the surface coverage by the adsorbed species also increased with the potential. Such behavior is in agreement with the relaxation of adsorbed species [56], [173]…”
Section: Electrochemical Impedance Diagrams At Ecorrsupporting
confidence: 84%